Capability Development Efforts of Human Resources in Furniture Industry at Leilem Village Minahasa Regency - Kalvin Salindeho Andaria; Xaverius E Lobja; Hermon Maurits Karwur; Recky H. E. Sendouw (Jurnal Ad'ministrare, 2020)
The main problem of research is the development of human resources to improve the ability of furniture industry workers at Leilem Village Minahasa Regency. The research objective is to find out the steps taken to improve the ability of workers as human resources to support work productivity of workers and to determine the obstacles faced in efforts to improve the ability of workers and to find out the efforts made to overcome obstacles related to develop resource capabilities in the furniture industry at Leilem village. The research method is qualitative. The technique of determining the data source sample namely, the main data collection procedures or techniques used were observation, interviews, documentation studies, and triangulation techniques. Data analysis uses steps from Milles and Huberman. Data analysis activities conducted in three stages, namely: first; data reduction, second; data display and third; drawing conclusions and verification. Data source: Government, furniture entrepreneurs, workers. Based on the results of the analysis and discussion of the results of the research, the following research conclusions can be put forward: 1) Important steps were taken by the manager of the furniture business unit at the village of Leilem to develop the ability of workers to plan development and develop workers. This is done due to workers are very important human resources and determine the progress of the business. 2) The obstacles are; lack of work motivation, the number of orders for goods from consumers, as a result, it is difficult to determine the time for worker coaching, and the length or, time to be spent by workers in doing furniture business jobs, consequently it is also difficult to determine the time for worker coaching. 3) Efforts made by the managers of the furniture industry business to overcome various obstacles encountered in increasing the ability of workers are by providing motivation to workers and managing work time for workers.